Lateral Control of Autonomous Vehicles with Data Dropout via an Enhanced Data-driven Model-free Adaptive Control Algorithm - Shida Liu; Yuhao Yan; Honghai Ji; Li Wang (Journal of Highway and Transportation Research and Development)
Addressing the lateral path tracking control issue of autonomous vehicles during data dropout, an improved model-free adaptive control system with data compensation (DC-EMFAC) is introduced. First, the method introduces a dynamic linearization technique with a time-varying factor pseudo gradient (PG) to linearize the dynamic process of an autonomous vehicle, and then designs a model-free adaptive controller. Moreover, addressing the issue of data dropout in the actual system, this paper employs an estimation algorithm to estimate the data loss at the present time based on the system 's input and output (I/O) from the past and PG. The advantage of the DC-EMFAC is that the controller design process is based on the I/O data of the controlled object, without the need for an accurate mathematical model. The effectiveness of the proposed algorithm is verified through a series of simulations on the Panosim platform.